TRANSFORMATION OF GEOGRAPHY EDUCATION IN THE DIGITAL ERA: EVALUATION OF GEOGRAPHY TEACHER READINESS THROUGH OUTCOME-BASED EDUCATION (OBE) APPROACH - Yohanes Ware; Hafiziani Eka Putri (Universitas Sebelas Maret (UNS), 2025)
This study aims to evaluate the readiness of geography teachers to apply digital technology and understand and implement the Outcome-Based Education (OBE) approach. The research method was a descriptive quantitative survey with data collection techniques through closed questionnaires and in-depth interviews. The research sample involved 88 geography teachers selected using a cluster sampling technique based on geographical location (Java Island and outside Java Island) and school type (public and private). Data analysis was conducted using descriptive statistical methods using SPSS software version 26. The results showed that teachers' digital readiness was in the good enough category, with basic understanding related to the use of technology obtaining the highest average score (Mean = 4.25). However, routine utilisation of technology, such as Geographic Information Systems (GIS) and e-learning, is still limited (Mean = 3.41). Supporting factors, such as confidence in integrating technology, had a relatively high score (Mean = 4.02), while the main obstacle of limited digital facilities and internet access recorded a score (Mean = 3.65). In addition, teachers' understanding of the OBE approach is also reasonably good (Mean = 3.49), especially in assessing student learning outcomes (Mean = 4.16). However, outcome-based learning planning still needs to be improved through continuous training programs. Curriculum support and implementation of project-based or case study-based learning strategies showed significant variations among respondents. Based on these results, this study recommends improving technological infrastructure, implementing applicable training, and strengthening the curriculum to encourage the transformation of education based on digital technology and the OBE approach.